Pelaksanaan Fungsi Perawatan Kesehatan Keluarga dengan Balita - Irwina Angelia Silvanasari; M. Elyas Arif Budiman (FORIKES, 2022)
The toddler aggregate is one of the vulnerable groups in the community and has a fairly high prevalence of health problems. The family has an important role in the implementation of the family health care function to support the achievement of the health status of children under five. The purpose of this study was to provide an overview of the implementation of the health care function of families with children under five. This research was a quantitative research with a cross sectional approach. The population of this study were all families with toddlers in Jatisari Village, Jenggawah District, Jember Regency. The sample size was 100 respondents who were selected by purposive sampling technique. The instrument used was a questionnaire about the function of health care for families with children under five. Data were analyzed descriptively in the form of frequency and percentage. The results showed that the function of health care for families with children under five had not been implemented by 45 respondents (45%) and had been implemented by 55 respondents (55%). The function of health care is related to the role of the family for the continuity of the health of the family. This family health care function includes the values held by the family in health, family definitions of health and illness, family health status and susceptibility to illness, family dietary practices, sleep rest habits, drug use habits in the family, preventive measures, family health history, perceptions of health services, emergency health services, sources of payment, and logistics for obtaining care. Nurses have an important role in optimizing the implementation of the health care function of families with toddlers. Nurses are expected to be able to provide education and increase parents' understanding of the implementation of the health care function of families with toddlers.Keywords: health care function; family; toddler; childABSTRAK Agregat balita merupakan salah satu kelompok rentan yang ada di masyarakat dan memiliki prevalensi masalah kesehatan yang cukup tinggi. Keluarga memiliki peran penting dalam pelaksanaan fungsi perawatan kesehatan keluarga untuk mendukung pencapaian status kesehatan balita. Tujuan penelitian ini adalah untuk memberikan gambaran pelaksanaan fungsi perawatan kesehatan keluarga dengan balita. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian ini adalah seluruh keluarga dengan balita di Desa Jatisari, Kecamatan Jenggawah, Kabupaten Jember. Besar sampel adalah 100 responden yang dipilih dengan teknik purposive sampling. Instrumen yang digunakan adalah kuesioner tentang fungsi perawatan kesehatan keluarga dengan balita. Data dianalisis secara deskriptif berupa frekuensi dan persentase. Hasil penelitian menunjukkan bahwa fungsi perawatan kesehatan keluarga dengan balita belum dilaksanakan oleh 45 responden (45%) dan sudah dilaksanakan oleh 55 responden (55%). Fungsi perawatan kesehatan terkait dengan peran keluarga demi kelangsungan kesejahteraan kesehatan keluarganya. Fungsi perawatan kesehatan keluarga ini mencakup nilai yang dianut keluarga dalam kesehatan, definisi keluarga tentang sehat sakit, status kesehatan keluarga dan kerentanan terhadap sakit, praktek diet keluarga, kebiasaan istirahat tidur, kebiasaan penggunaan obat-obatan dalam keluarga, tindakan preventif, riwayat kesehatan keluarga, persepsi tentang pelayanan kesehatan, pelayanan kesehatan darurat, sumber pembayaran, dan logistik untuk mendapatkan perawatan. Perawat memiliki peran yang penting dalam mengoptimalkan pelaksanaan fungsi perawatan kesehatan keluarga dengan balita. Perawat diharapkan mampu memberikan edukasi dan meningkatkan pemahaman orang tua tentang pelaksanaan fungsi perawatan kesehatan keluarga dengan balita.Kata kunci: fungsi perawatan kesehatan; keluarga; balita; anak